On the Diophantine equation - Zahari, N. M.; Sapar, Siti Hasana; Mohd Atan, Kamel Ariffin (AIP Publishing LLC, 2012)
This paper discusses an integral solution (a, b, c) of the Diophantine equations x3n+y3n = 2z2n for n ≥ 2 and it is found that the integral solution of these equation are of the form a = b = t2, c = t3 for any integers t.